Pengaruh Gaya Kepemimpinan Otokratik terhadap Budaya Kerja Karyawan PT Wira Sandi di Jakarta - Suswandari Suswandari (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2010)
This research conducted in order to understand the relationship and the impacts between autocratic leadership style applications towards some efforts for changing, improving and maintaining employees working culture in PT. Wira Sandi. The researched variables were the applications of autocratic leadership style as independent variable and employees working culture (security guard members) in PT Wira Sandi (Security Service Agency) as dependent variable. Data were collected by observations, interviews, and questioners which were involving of 80 respondents as the sample from 807 populations (Security Guard Members) of PT Wira Sandi which employed by 24 clients (Security Service Users). The extended regression equation of this research resulting Y= 13.48 + 0. 71X, correlation coefficient r = 0.84 and determinant coefficient r2 = 71.1 %. Furthermore, after testing correlation coefficient parameters which founded to be positively and significantly related and influenced the autocratic leadership style towards working culture by 71.1%. Determination coefficient value shows that formed working culture can be explained by autocratic leadership style variable. Whereas, the rest 28% were explained by other variables which were also impacting employees working culture, but not explained by this research